Structure, Function and Regulation of a Second Pyruvate Kinase Isozyme in Pseudomonas aeruginosa - Abdelhamid, Yassmin; Wang, Meng; Parkhill, Susannah L.; Brear, Paul; Chee, Xavier; Rahman, Taufiq; Welch, Martin (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa (PA) depends on the Entner-Doudoroff pathway for glycolysis. The main enzymatic pacemaker of the lower half of the Entner-Doudoroff pathway is pyruvate kinase. PA encodes two isoforms of pyruvate kinase, denoted PykAPA and PykFPA. In other well-characterized organisms containing two pyruvate kinase isoforms (such as Escherichia coli) each isozyme is differentially regulated. The structure, function and regulation of PykAPA has been previously characterized in detail, so in this work, we set out to assess the biochemical and structural properties of the PykFPA isozyme. We show that pykFPA expression is induced in the presence of the diureide, allantoin. In spite of their relatively low amino acid sequence identity, PykAPA and PykFPA display broadly comparable kinetic parameters, and are allosterically regulated by a very similar set of metabolites. However, the x-ray crystal structure of PykFPA revealed significant differences compared with PykAPA. Notably, although the main allosteric regulator binding-site of PykFPA was empty, the “ring loop” covering the site adopted a partially closed conformation. Site-directed mutation of the proline residues flanking the ring loop yielded apparent “locked on” and “locked off” allosteric activation phenotypes, depending on the residue mutated. Analysis of PykFPA inter-protomer interactions supports a model in which the conformational transition(s) accompanying allosteric activation involve re-orientation of the A and B domains of the enzyme and subsequent closure of the active site.